Perception of Farmers in Seaweed Farming Business in Seriwe Village, East Lombok Regency - Rosyidah, Lathifatul; Zamroni, Achmad; Apriliani, Tenny (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2019)
Most of the coastal communities at Seriwe Village, East Lombok Regency have livelihoods as seaweed cultivators. The government has launched various programs to improve the productivity and economy of the community through seaweed farming. The objectives of the study are: 1) to know the characteristics of seaweed farming in East Lombok, 2) to analyze the perception of cultivators on the development of seaweed cultivation, and 3) to analyze the perception of farmers on stakeholder participation in the development of seaweed cultivation. This research was conducted in Seriwe Village, Jero Waru District in 2018 using survey methods. The type of data collected is primary data and secondary data. Data analysis uses descriptive methods and simple statistical analysis. In general, seaweed cultivation by farmers is good. The results showed that people's perceptions of all seaweed farming activities were in a good category.